Luminescent protein staining with Re(i) tetrazolato complexes - Fiorini, V.; Bergamini, L.; Monti, N.; Zacchini, S.; Plush, S.; Massi, Massimiliano; Hochkoeppler, A.; Stefan, A.; Stagni, S. (R S C Publications, 2018)
Within the general framework of our past and current studies dealing with the investigation of the photophysical properties and the biological behavior of the family of tetrazolato and tetrazole Re(i) complexes, we have endeavored to investigate their potential in the luminescent staining of proteins purified by acrylamide gel electrophoresis. With the aim to provide the first examples of luminescent Re(i) complexes to be exploited for this specific purpose, we have designed and prepared four new Re(i)-based species with the general formula fac-[Re(CO)3(N^N)(Tph)]2-/0, where Tph is the 5-(phenyl)tetrazolato anion and N^N is in turn represented by bathophenanthroline disulfonate (BPS), bathocuproine disulfonate (BCS) or by the SO3-free bathocuproine (BC). In this latter case, the neutral complex fac-[Re(CO)3(BC)(Tph)] served as a model species for the characterization of the former disulfonate complexes. Its cationic analogue fac-[Re(CO)3(BC)(Tph-Me)]+was also prepared by a straightforward methylation reaction. All complexes displayed bright phosphorescence in organic media and, relative to their water solubility, the dianionic species fac-[Re(CO)3(BPS)(Tph)]2-and fac-[Re(CO)3(BCS)(Tph)]2-were also highly emissive in aqueous solution. The sulfonate groups played a key role in promoting and significantly enhancing the luminescent staining performances of both the Re(i) complexes fac-[Re(CO)3(BPS)(Tph)]2-and fac-[Re(CO)3(BCS)(Tph)]2-for proteins. Highlighting a response superior to that of Coomassie Blue and comparable to the one obtained by the well-known silver staining method, these dianionic Re(i)-complexes could efficiently detect up to 50 ng of pure Bovine Serum Albumin (BSA), as well as all proteins found in a Standard Protein Marker mix and from a total protein extract. A lower but still good response for luminescent protein staining was surprisingly obtained by employing the-SO3-free neutral and cationic complexes fac-[Re(CO)3(BC)(Tph)] and fac-[Re(CO)3(BC)(Tph-Me)]+, respectively. These preliminary results open up new possibilities for the further widening of the use of Re(i)-based complexes as luminescent protein staining agents.